Online And Conventional Transportation Policy In Indonesia (Analysis Of Equitable Policy Alternatives For Community Welfare) - M. Afif Hasbullah; Nisaul Barokati Seliro Wangi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Online transportation in the period of the fourth industrial revolution provides convenience and accessibility, but it also causes social conflicts with conventional transportation such as motorcycle taxis, taxis, and public transportation. This study investigated the regulation of online and conventional transportation in Indonesia using a community-based approach.The study concluded that the government lacked a good public policy development model other than the stimulus reaction. Since policies were made after problems arose, they were considered ineffective. Based on the analysis and scoring, possible alternatives were recommended for being implemented such as: Online and Conventional Transportation Business Actors, Conventional Transportation Stimulus towards Online; and Changes to Regulations.